A Review of Management Guidelines of Environmentally Friendly Hotel - Sungthong, Sirinthra; Pattanapokinsakul, Kanyapat; Soonsan, Nimit (Arts of Management Journal, 2024)
An approach to hotel management that is environmentally friendly must have elements in many aspects, such as green hotel management factors that are guidelines for environmental preservation. Most hotels focused on planning for space usage, such as reducing the use of resources, reducing costs, and saving energy. This study aimed to review the management guidelines of environmentally friendly hotel. According to the study, it was found that successful hotels are green hotels that are friendly to the environment. Most of them start with the support and participation of business owners, entrepreneurs, consumers, local people, people in the community, and the government to promote environmental conservation, organizing training for personnel, and the participation of all sectors in thinking together and supporting activities to reduce resource use and have a good attitude towards environmental conservation. However, the hotel business’s success in environmental management depends on management. Participation using environmental conservation policies and criteria as indicators in various forms, such as environmentally friendly services, personnel development, and procurement side management. There is even environmental and energy management, which are reuse, reduce, and recycle, which is in line with the criteria so that the hotel can be efficient and have good standards in the future. This is considered an important indicator of a green hotel that preserves the environment in a sustainable manner. The result of this study will be beneficial to all sectors. Especially in the hotel business sector, applying the results of the study to planning environmental management in hotels and creating a new attitude for personnel by paying attention to the importance of and reviewing environmental practices. along with providing quality service.